DEKONSTRUKSI PERAN PUSTAKAWAN - Wiji Suwarno (UIN Imam Bonjol Padang, 2019)
This takes the theme of writing about the role of librarian in the time of disrupsi. This research uses qualitative research with approach of Phenomenology. Informants from this research is the Librarian of all the elements for a visit and found in IAIN Salatiga taken random. Data collection was conducted using interviews and documents. The issue of this study is a strategy of adaptation to shifting the role of threatening perkembangangan librarian. The results of this research is that librarians are required to map out the development of, and dimilinya weaknesses, and develop the skills that are required in accordance with the development. This librarian been reliability advanced keprofesiannya that are then oriented on the ability of maintaining quality themselves. That competence is the ability in terms of Listening, Informatin acceptance, Public relation, Social relationship, Time management, Interpersonal, and Communication skills.